THE CONCEPT OF CARBON POLYGONS AND PERSPECTIVES OF THEIR FURTHER DEVELOPMENT IN ARMENIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2023)
A network of carbon polygons has been established in Russia to study the emission and uptake of greenhouse gases in natural ecosystems and to develop technological solutions to control the fluxes of greenhouse gases in natural ecosystems with the aim of reducing their emission and increasing their uptake from the atmosphere. The pilot project is an important part of the low-carbon development strategy to decarbonize the Russian economy, adapt the economy to the global energy transition, reduce greenhouse gas emissions and achieve carbon neutrality in Russia by 2060. To achieve these goals, the pilot project uses an integrated approach that includes ground-based measurements of carbon balance and greenhouse gas fluxes, remote sensing data, and mathematical modeling methods. To provide observations of greenhouse gas fluxes, a wide range of experimental methods for direct and indirect measurements of greenhouse gas fluxes will be used. Direct field flux measurements include eddy covariance and chamber methods. Carbon polygons for monitoring greenhouse gas fluxes are planned to be distributed in the most representative natural terrestrial and aquatic ecosystems, allowing to assess the spatial and temporal variability of greenhouse gas emission and uptake. The territory of Armenia is a unique region in terms of diversity of climatic conditions and landscapes. The development of a system for monitoring greenhouse gas fluxes can serve as a guarantee of obtaining representative data on the emission and absorption of greenhouse gases by natural ecosystems, with the perspective of Armenia achieving carbon neutrality in the coming decades.
Keywords: fluxes of greenhouse gases; network of carbon polygons; monitoring, emissions and absorption